Pencemar Mikroplastik dalam Air dan Sedimen Sungai Sail di Kota Pekanbaru - Fidela Raissa Widyadhanaa; Budijono Budijono; Yudho Harjoyudanto; Andri Hendrizal (Jurnal Fisika Unand, 2024)
This study aims to determine the type and abundance of microplastics in the water and sediment of the Sail River. This study was conducted from January 2024 to April 2024. Sampling was carried out once a month for three months at 3 stations, namely: Station 1 (Jalan Akasia), Station 2 (Jalan Hangtuah), Station 3 (Jalan Sumber Sari). Microplastic samples in water and sediment were analyzed at the Waste Treatment Laboratory of the Faculty of Fisheries and Marine Sciences, University of Riau.. The research results found 4 types of microplastics per station in both water and sediment, with the most common types being fibers in water and fragments in sediment. The total abundance of microplastics in water ranges from 216.67 – 280 particles/m3 and sediment ranges from 4,006.67 – 4,720 particles/kg. It was concluded that there was no difference in the total abundance of microplastics in either water or sediment between the stations studied.